TRADITIONAL MUSIC IN THE CONTEXT OF INTANGIBLE CULTURAL HERITAGE OF CENTRAL ASIA (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Modern traditional musical culture is considered as a whole, in the unity of historical-cultural, sociological, ethical-aesthetic and musical-stylistic approaches, and the existence, preservation and development of cultural traditions of the peoples of the region in the conditions of modernity in the context of current world trends in the study and protection of the intangible cultural heritage of mankind. National cultural heritage (folklore and oral-professional music) is a phenomenon of oral culture, the formation and development itself (including existence and protection), as well as the performing originality are fixed only by tradition.
Keywords: music, heritage, tradition, performing culture, existence, preservation, development.